TIME ACCELERATION OF UNDERSTRUCTURE WORKS WITH FAST TRACK METHOD ZONING-BASED (CASE STUDY: TRANSIT ORIENTED DEVELOPMENT LIGHT RAIL TRANSIT JAKARTA PHASE I PROJECT) - Lusiana Indarwati; Yusuf Latief (AIBPM Publisher, 2019)
Light Rail Transit (LRT) Jakarta Phase I construction has a special purpose of launching Asian Games 18th on August 10th, 2018. In fact, this time cannot be achieved due to decision of design in Transit Oriented Development (TOD) building but it is a critical path of the overall schedule. Therefore, zoning is made with the fast track method. The purposes of this study are to develop dominant factors of making zoning, to develop fast track method with zoning-based and the proper form of zoning. The results are making zoning will be determined by manpower capacity and its risk and a grid-shape of zoning is a match in an acceleration of understructure work because the overall duration can reduce 41 days.